PENGARUH PENERAPAN MODEL CREATIVE PROBLEM SOLVING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XII MIPA SMAN 5 PADANG - FAUZI NAFRI (Departemen Matematika, 2018)
The problem in learning matheamatic is the mathematical problem solving skills of student are not optimal. Low in mathematical problem solving skills occur in class XII MIPA SMAN 5 Padang.That problem can occur causes by some reason, such as the students still not active in learning mathematic and the students are not used to handling nonroutine questions. Creative Problem Solving is one of the learning model that can enhance the students mathematical problem solving skills. The purpose of this research is to describes the mathematical problem solving skills of students who study with Creative Problem Solving Learning models. This type of research is quasy-experiment with Randomized Control Group Only Design. The result of this research indicate that the mathematical problem solving skills of student whith application of Creative Problem Solving learning models is better than the mathematical problem solving skills students whith conventional learning. it can be conclude that there is an influence the application of Creative Problem Solving learning models to the mathematical problem solving skills.Keywords— Creative Problem Solving learning models, conventional learning, mathemaical problem solving skills